Optimization of horseradish peroxidase immobilization on glassy carbon electrode based on maize tassel-multiwalled carbon nanotubes for sensitive copper(II) ion detection - Moyo, Mambo; Okonkwo, Jonathan O.; Agyei, Nana M. (ESG, 2016)
Enzymatic procedures for measuring trace metal ions, based on the inhibitive action of these metals on horseradish peroxidase (HRP) enzyme activity, have been developed. Glassy carbon electrode (GCE) modified with maize tassel- multiwalled carbon nanotubes (MT-MWCNT) was used as an immobilizing surface of HRP through electrostatic attractions. The voltammetric and amperometric response of HRP was affected by the presence of metal ion, which caused a decrease in the current intensity. The experimental optimum working conditions of MT: MWCNT amount (10 μL, 4:1), enzyme loading (10 μL, 10 mg mL-1), nafion amount (0.5 μL, 0.3%), pH 7, and potential applied (- 300 mV) were established. Using Cu2+ as a model divalent metal ion, the inhibition rate was proportional to the concentration in the range from 0.068-2.0 mg L-1 with a limit of detection of 4.2 μg L-1. Representative Dixon and Cornish-Bowden plots showed that the reaction was reversible and mixed. Under these conditions, repeatability and reproducibility of HRP/MT-MWCNT biosensor was determined, reaching values below 10% in terms of relative standard deviation.